Influence of Tumor Histology on Preoperative Staging Accuracy of Breast Metastases to the Axilla. Issue 1 (27th November 2012) - Hackney, Lisa; Williams, Susan; Bajwa, Saba; Morley‐Davies, Adrian J; Kirby, Robert M.; Britton, Ingrid
Abstract Histologic confirmation of axillary nodal metastases preoperatively avoids a sentinel node biopsy and enables a one step surgical procedure. The aim of this study was to establish the local positive predictive value of axillary ultrasound (AUS) and guided needle core biopsy (NCB) in axillary staging of breast cancer, and to identify factors influencing yield. A prospective audit of 142 consecutive patients (screening and symptomatic) presenting from 1st December 2008–31st May 2009 with breast lesions categorized R4–R5, who underwent a preoperative AUS, and proceeded to surgery was undertaken. Ultrasound‐guided NCB was performed on nodes radiologically classified R3–R5. Lymph node size, number, and morphological features were documented. Yield was correlated with tumor size, grade, and histologic type. AUS/NCB was correlated with post surgical pathologic findings to determine sensitivity, specificity, positive and negative predictive value of AUS and NCB. A total of 142 patients underwent surgery, of whom 52 (37%) had lymph node metastases on histology. All had a preoperative AUS, 51 (36%) had abnormal ultrasound findings. 46 (90%) underwent axillary node NCB of which 24 (52%) were positive. The smallest tumor size associated with positive nodes at surgery was 11.5 mm. The sensitivity of AUS was 65%. Specificity was 81%, with a positive predictive value (PPV) of 67% and negative predictive (NPV) value of 80%. Sensitivity of U/S‐guided NCB was 75%, with a specificity of 100%, PPV 100% and NPV 64%. Sensitivity of AUS for lobular carcinoma was 36% versus 76% for all other histologies. Sensitivity of NCB for lobular cancer was 33% versus 79% for all other histologies. The most significant factor producing discordance between preoperative AUS and definitive histologic evidence of lymph node metastasis was tumor type. Accurate preoperative lymph node staging was prejudiced by lobular histology (p < 0.0019).